Family-Driven Support: An Intervention For Successful Exclusive Breastfeeding - Mauliyah, Ihda; Indah Kartikasari, Ratih; Alifiana Rahmawati, Shinta (Jurnal Surya, 2025)
ABSTRACT Introduction: Exclusive breastfeeding during the first six months of life is important for infant growth and development, yet national coverage in Indonesia remains below the target. Low family support for breastfeeding mothers is one of the contributing factors. To develop and evaluate the Family-Driven Support model, an intervention that actively involves the immediate family (husband and mother/mother-in-law) to improve exclusive breastfeeding success. Methods: This study used a quasi-experimental design with a pretest–posttest control group, involving 30 mother-family pairs in the working area of Karanggeneng Community Health Center, Lamongan (15 intervention, 15 control). The intervention included family education classes, couple counseling, digital support via WhatsApp Group, and distribution of a family education booklet. Data were collected using knowledge, attitude, and practice (KAP) questionnaires on family support and indicators of exclusive breastfeeding achievement. Results: Initial results showed that most families had moderate knowledge (70%), neutral attitudes (63.3%), and low support practices (83.3%). The Family-Driven Support intervention did not significantly improve knowledge (p = 0.090), but successfully enhanced attitudes (p < 0.001) and support practices (p < 0.001) toward exclusive breastfeeding Conclusion: The Family-Driven Support model has the potential to be an innovative and replicable approach to strengthen family–healthcare collaboration in supporting exclusive breastfeeding success. Keywords: Family Driven Support, Exclusive breastfeeding, Intervention